Molecular Mechanisms of Bipolar Disorder: Progress Made and Future Challenges - Kim, Yeni; Santos, Renata; Gage, Fred H.; Marchetto, Maria C. (Frontiers in Cellular Neuroscience, 2017)
Bipolar disorder (BD) is a chronic and progressive psychiatric illness characterized by mood oscillations, with episodes of mania and depression. The impact of BD on patients can be devastating, with up to 15% of patients committing suicide. This disorder is associated with psychiatric and medical comorbidities and patients with a high risk of drug abuse, metabolic and endocrine disorders and vascular disease. Current knowledge of the pathophysiology and molecular mechanisms causing BD is still modest. With no clear biological markers available, early diagnosis is a great challenge to clinicians without previous knowledge of the longitudinal progress of illness. Moreover, despite recommendations from evidence-based guidelines, polypharmacy is still common in clinical treatment of BD, reflecting the gap between research and clinical practice. A major challenge in BD is the development of effective drugs with low toxicity for the patients. In this review we focus on the progress made and future challenges we face in determining the pathophysiology and molecular pathways involved in BD, such as circadian and metabolic perturbations, mitochondrial and endoplasmic reticulum dysfunction, autophagy and glutamatergic neurotransmission; which may lead to the development of new drugs.